Overmacht: Analisis Yuridis Penundaan Pelaksanaan Prestasi Akibat Pandemi Covid-19 - Tauratiya Tauratiya (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
On March 14, 2020, the government of the Republic of Indonesia declared the Covid-19 pandemic a National Disaster. The entire community was urged to stay at home or work remotely. This situation has rendered the daily activities of both the community and the government, including schooling, work, trade, and others, ineffective and delayed. Furthermore, it has also impacted corporate activities at both national and global levels. Many businesses have been disrupted due to the implementation of Large-Scale Social Limitations policy, thereby preventing companies or individuals from fulfilling their previous agreements. This study investigates whether the Covid-19 pandemic can serve as a legitimate reason for individuals or companies to delay the fulfillment of their obligations, considering it as a force majeure, and its legal implications. This research adopts a qualitative-library approach with a juridical-normative perspective. The findings indicate that force majeure is akin to the concept of overmacht, signifying a situation where the debtor cannot be held accountable due to circumstances beyond their control and not resulting from negligence. The concept of overmacht is governed by Article 1244 and Article 1245 of the Civil Code. The Covid-19 pandemic falls under the category of force majeure, thus enabling debtors to invoke it as a valid reason to postpone or refrain from fulfilling their obligations as per agreements, provided they can demonstrate that their failure to comply is not attributable to them, but rather to unforeseeable and inevitable circumstances.